Evaluating the Effectiveness, Safety, and Satisfaction Rates of Phenol 90%, Trichloroacetic Acid 100%, and Radiofrequency in Lateral Matricectomy for the Treatment of Ingrown Toenails: A Triple‐Arm Clinical Trial - Mohammadreza Ghassemi; Zahra Keshavarz; Elham Behrangi; Afsaneh Sadeghzadeh Bazargan; Alireza Jafarzadeh; Azadeh Goodarzi (Health Science Reports)
ABSTRACT Background and Aims This study aimed to evaluate the effectiveness, safety, and satisfaction rates of three different lateral matricectomy methods for treating ingrown toenails: 90% phenol, 100% trichloroacetic acid (TCA), and radiofrequency (RF) ablation. Our objective was to identify which method offers superior outcomes regarding postoperative pain, healing time, aesthetic results, and complication rates. Methods Conducted between August 2022 and June 2023, the study included 12 eligible patients divided into three groups: Group 1 underwent lateral matricectomy with 90% phenol, Group 2 with 100% TCA, and Group 3 with RF treatment. Preoperative assessments were conducted, and patients were followed up on the day after surgery and at Weeks 1, 2, and 3, as well as at Months 1, 2, 6, and 9 postoperatively (totaling nine assessments). Pain levels were measured using the Visual Analog Scale (VAS), while wound discharge and bleeding were rated on specified scales. Results Mean pre‐ and postoperative (second day) pain scores were 6.0 ± 3.3 and 0.75 ± 0.67 for Group 1, 6.25 ± 4.92 and 1.75 ± 0.58 for Group 2, and 6.25 ± 2.25 and 3.50 ± 0.50 for Group 3, with significant differences observed. RF treatment showed higher moderate postoperative pain compared to mild pain in the phenol and TCA groups. Average healing time was 22.75 ± 3.50 days (phenol), 40 ± 12.91 days (TCA), and 26.25 ± 6.70 days (RF), with phenol demonstrating faster healing, although differences were statistically insignificant. The median aesthetic outcomes favored phenol with a score of 5.0. Conclusion Lateral matricectomy with 90% phenol, 100% TCA, and RF all provide unique advantages for ingrown toenail treatment. Phenol exhibited high success rates, minimal complications, faster healing, and excellent aesthetic outcomes. Trial Registration IRCT, IRCT20220228054152N1. Registered 03 January 2023, https://www.irct.behdasht.gov.ir/trial/65907.